Effect of indomethacin treatment upon actively-induced and transferred experimental allergic encephalomyelitis (EAE) in Lewis rats. - Ovadia, H (1982)
Daily administration of indomethacin (5 mg/kg) to Lewis rats from day 7 through day 21 following sensitization to guinea-pig spinal cord neural antigen plus Freund's complete adjuvant (FCA) resulted in an aggravation of clinical signs of EAE accompanied by a higher mortality. In contrast, lymph node cells (LNC) from sensitized and drug-treated donor rats showed decreased EAE transfer activity. The in vitro Con A response of LNC from sensitized, indomethacin-treated rats was comparable to those of normal LNC or LNC from sensitized animals only. The spleen cell response of sensitized rats was significantly lower than the response seen in normal animals, but was returned to normal levels in sensitized, indomethacin-treated animals. We believe these observations reflect an indomethacin-mediated diminished accumulation of EAE effector cells within peripheral lymph node tissues together with abrogation of splenic suppressor cell activity by indomethacin-mediated inhibition of prostaglandin (PG) synthesis in Lewis rats sensitized and treated with this drug under the conditions defined.